The purchase behavior of the consumer - Ramona Mihaela Urziceanu; Simona-Valentina Pașcalau (Agora International Journal of Economical Sciences (AIJES), 2016)
The paper describes the types of purchase behavior of consumers and the stages of decision made by the purchasing of the consumer, the approach in which the personal factors can affect the decision made by the purchasing of the consumer, the psychological factors which can affect the decision made by the purchasing of the consumer, the examination of the social factors that influence the decision made by the purchasing of the consumer and whyA\^~ is it so important that marketing has to understand consumer purchasing behavior.
Keywords: 330